Kemampuan Interpretasi Grafik Siswa Sekolah Swasta di Thailand Selatan Pada Materi Kinematika Gerak Dalam Pembelajaran Fisika - Luedo, Matofee; Supeno, Supeno; Maryani, Maryani (Jurnal Penelitian Pendidikan Fisika, 2021)
The purpose of this study was to determine the student's ability to interpret graphics on motion kinematics material. The research was conducted in four private schools, namely the Thamavitya School in Yala Province, the Romanian School in Naratiwatn Province, the Azizstan Foundation School in Pattani Province, and the Seangtam Wittaya Foundation School in Senggora Province. Research respondents were class X IPA students in the even semester of 2019/2020 with a total of 160 people. The research instrument was a test in the form of multiple choice questions along with 10 points of reasons. The results showed that in general the students' ability to interpret graphics on the motion kinematics material was categorized less. In detail, the results show that the ability to determine the meaning of gradients on categorized graphs is very lacking, the ability to determine data from a range of categorized variables is sufficient, the ability to determine data on independent and dependent variables on categorized graphs is lacking, the ability to determine relationships between variables on categorized graphs is lacking.